Beyond Face and Voice: A Review of Alexithymia and Emotion Perception in Music, Odor, Taste, and Touch - Suslow, Thomas; Kersting, Anette (Frontiers in Psychology, 2021)
Alexithymia is a clinically relevant personality trait characterized by deficits in recognizing and verbalizing one’s emotions. It has been shown that alexithymia is related to an impaired perception of external emotional stimuli, but previous research focused on emotion perception from faces and voices. Since sensory modalities represent rather distinct input channels it is important to know whether alexithymia also affects emotion perception in other modalities and expressive domains. The objective of our review was to summarize and systematically assess the literature on the impact of alexithymia on the perception of emotional (or hedonic) stimuli in music, odor, taste, and touch. Eleven relevant studies were identified. On the basis of the reviewed research, it can be preliminary concluded that alexithymia might be associated with deficits in the perception of primarily negative but also positive emotions in music and a reduced perception of aversive taste. The data available on olfaction and touch are inconsistent or ambiguous and do not allow to draw conclusions. Future investigations would benefit from a multimethod assessment of alexithymia and control of negative affect. Multimodal research seems necessary to advance our understanding of emotion perception deficits in alexithymia and clarify the contribution of modality-specific and supramodal processing impairments.